Hypoglycemic treatment of diabetic patients in the Emergency Department - Carmen Caballero Requejo; Elena Urbieta Sanz; Abel Trujillano Ruiz; Celia García-Molina Sáez; María Onteniente Candela; Pascual Piñera Salmerón (Elsevier, 2016)
Objectives: To analyze if the hypoglycemic therapy prescribed in the Emergency Department adapts to the consensus recommendations available, as well as to assess its clinical impact. Methods: A descriptive observational study, which included patients awaiting hospital admission, who were in the Observation Ward of the Emergency Department and had been previously diagnosed with diabetes mellitus, and were receiving treatment with hypoglycemic drugs at home. The management of antidiabetic treatment and its clinical impact were assessed. Results: 78 patients were included. At admission to the Emergency Department, treatment was modified for 91% of patients, and omitted for 9%. The most prescribed treatment was sliding scale insulin (68%). The treatments prescribed coincided in a 16.7% with the recommendations by the Spanish Society of Emergency Medicine. After intervention by the Pharmacist, the omission descended to 1.3%, and the adaptation to the recommendations increased to 20.5%. Comparing patients whose treatment coincided with the recommendations and those who did not, the clinical impact was respectively: mean glycemia at 24 hours: 138.3 } 49.5 mg/dL versus 182.7 } 97.1 mg/dL (p = 0.688); mean rescues with insulin lispro: } 1.6 versus 1.5 } 1.8 (p = 0.293); mean units of insulin lispro administered: 4.6 } 12.7 IU versus 6.6 } 11.3 IU (p = 0.155). Conclusions: We found antidiabetic prescriptions to have a low adaptation to consensus recommendations. These results are in line with other studies, showing an abuse of sliding scale regimen as single hypoglycemic treatment